EVALUATION OF SUNFLOWER, Helianthus annus L. GERMPLASM ACCESSIONS AGAINST LEAFHOPPER, Amrasca biguttula biguttula Ishida UNDER FIELD CONDITIONS - G. SRIDEVI, D. SHIVANI; BHARATI BHAT, TABASSUM FATIMA, P. SATYA SRINIVAS (The Journal of Research, PJTSAU, 2021)
Field experiment was conducted during Rabi season 2016-17 and 2017-18 to screen 57 sunflower germplasm accessions along with commercial hybrid, Syngenta SB-275 and susceptible check, Morden to evaluate their reaction against sunflower leafhopper at ICAR-Indian Institute of Oilseeds Research (IIOR), Hyderabad, India. Based on mean scale index (MSI) the accessions were categorised as highly resistant, resistant, moderately resistant, susceptible and highly susceptible. During Rabi 2016-17, average leafhopper infestation ranged between 0.3 and 18.2 per three leaves per plant across the germplasm accessions. TSG- 349 recorded the lowest mean population of leafhoppers (0.3 per three leaves per plant) while highest number of leafhoppers were recorded on the susceptible check, Morden (18.2 per three leaves per plant), 22 accessions were found resistant, 25 were found moderately resistant and 10 were found susceptible. During Rabi, 2017-18, leafhopper infestation ranged between 2.2 and 32.4 per three leaves per plant. GMU-339 recorded the lowest mean population of leafhoppers (2.2 per three leaves per plant). Whereas, highest numbers of leafhoppers were recorded on the susceptible check, Morden (32.4 per three leaves per plant), 15 germplasm lines were categorized as resistant, 30 germplasm lines were identified as moderately resistant while to be 12 were susceptible. Considering both the years, consistently 15 accessions were identified as resistant and 23 accessions moderately resistant.